2007
DOI: 10.1002/bjs.5863
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve of combined modality treatment in peritoneal surface disease

Abstract: The learning curve of combined modality treatment for peritoneal surface disease is long, and reflects patient selection and treatment expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(150 citation statements)
references
References 31 publications
9
133
1
7
Order By: Relevance
“…Over the years, reduction of post-operative mortality has been reported from tertiary centres worldwide. Moran reported a decreased mortality rate from 18 % down to 3 % [11,30], The Netherlands Cancer Institute reported a decrease in mortality from 8 % to 4 % [9], and Yan et al reported a decrease from 7 % to 1 % [10], all of which point towards the strong influence of the learning curve.…”
Section: Importance Of Blearning Curvetmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the years, reduction of post-operative mortality has been reported from tertiary centres worldwide. Moran reported a decreased mortality rate from 18 % down to 3 % [11,30], The Netherlands Cancer Institute reported a decrease in mortality from 8 % to 4 % [9], and Yan et al reported a decrease from 7 % to 1 % [10], all of which point towards the strong influence of the learning curve.…”
Section: Importance Of Blearning Curvetmentioning
confidence: 99%
“…Several studies showed that pulmonary complications can be reduced by local experience, better peri-operative fluid and glycemic control and multi-disciplinary management of patients undergoing CRS and HIPEC [9,[30][31][32].…”
Section: Pulmonary Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIPEC has a well demonstrated learning curve. [72] Over the years, the morbidity and mortality of this procedure has declined and is comparable to that of CRS alone. Table 4 lists that morbidity and mortality rates reported in various studies with HIPEC for ovarian cancer.…”
Section: Morbidity and Mortality Of Crs And Hipec In Ovarian Cancermentioning
confidence: 99%